Prevalence and Distribution of Risk Factors for Preterm Labor in RSUP DR. Mohammad Hoesin Palembang Period January 1 2020 – December 31 2023 - Beumaputra, Adyatma Utama; Martadiansyah, Abarham; Nurwany, Raissa; Mirani, Putri; Putra, Hadrians Kesuma (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aims to determine the prevalence and distribution of risk factors for preterm labor.Methods: This is a descriptive observational study with a cross-sectional design. The data used in this study were secondary data obtained with the total sampling method from the medical records of Dr. Mohammad Hoesin Palembang Hospital from January 1, 2020 to December 31, 2023.Results: This study found 1,654 cases of preterm labor from January 1, 2020 to December 31, 2023. The analysis of risk factors among mothers indicated that those within the high-risk age categories (<20 years and >35 years) constituted 31.7%. Multiparous and grand multiparous women represented 41.7%, while multiple pregnancies accounted for 6.6%. A history of premature rupture of membranes was noted in 25.4% of cases, polyhydramnios was observed in 1.3%, and a history of cesarean delivery was found in 25.4%. Furthermore, 33% suffered from hypertension, and 2.5% had diabetes. Anemia was prevalent in 47.9% of the mothers, and infection was reported in 42.8%. A history of preterm delivery was noted in 13.7%, risky gestational distance was found in 10.6%, and 25% had a history of antepartum hemorrhage. Finally, obesity was observed in 14.5% of the mothers.Conclusion: The number of deliveries continued to decrease, but the prevalence of preterm labor increased from 2020 to 2023. Anemia is the most common risk factor found in mothers with preterm labor.Prevalensi dan Distribusi Faktor Risiko Persalinan Prematur di RSUP Dr. Mohammad Hoesin Palembang dalam Tiga TahunAbstrakTujuan: Penelitian ini bertujuan untuk mengetahui prevalensi serta distribusi faktor risiko persalinan prematur.Metode: Penelitian ini merupakan penelitian deskriptif observasional dengan desain cross-sectional. Data yang digunakan dalam penelitian ini merupakan data sekunder dengan metode total sampling dari data rekam medik RSUP Dr. Mohammad Hoesin Palembang periode 1 Januari 2020 – 31 Desember 2023.Hasil: Terdapat 1654 kasus persalinan prematur dengan periode 1 Januari 2020 – 31 Desember 2023. Distribusi faktor risiko didapatkan ibu dengan usia berisiko (<20 tahun dan >35) tahun (31,7%), paritas multipara dan grandemultipara (41,7%), kehamilan multipel (6,6%), riwayat ketuban pecah dini (25,4%), polihidramnion (1,3%), riwayat persalinan sesar (25,4%), hipertensi (33%), diabetes (2,5%), anemia (47,9%), infeksi (42,8%), riwayat persalinan prematur (13,7%), jarak kehamilan berisiko (10,6%), riwayat perdarahan antepartum (25%), obesitas (14,5%). Kesimpulan: Jumlah persalinan terus mengalami penurunan, namun prevalensi kejadian persalinan prematur terus mengalami peningkatan dari tahun 2020-2023. Anemia menjadi faktor risiko paling banyak yang ditemukan pada ibu dengan persalinan prematur.Kata kunci: Prevalensi, Persalinan Prematur, Faktor Risiko